Acoustic insights into the Rhinella marina group: revisiting the advertisement calls of two closely related species (Anura: Bufonidae) - Parreira, Isabella; Andrade, Felipe Silva De; Costa-Campos, Carlos Eduardo; Giaretta, Ariovaldo Antonio (Zootaxa, 2025)
The Rhinella marina group comprises 11 species distributed across open and forested habitats from the southern United States to Uruguay. Previous descriptions of the advertisement calls of R. diptycha and R. marina were based on limited sample sizes and a narrow range of acoustic variables. Here, we documented the first advertisement call description of R. marina from Brazil, while the recordings from Rondônia constitute the westernmost acoustic record of R. diptycha in northern Brazil. We also compiled existing data on the advertisement calls of R. marina and R. diptycha and compared these calls with those described for other species within the R. marina group. To search for discrimination among R. marina and R. diptycha, we used the Random Forest (RF) model and Wilcoxon-Mann-Whitney Rank Test. Our analysis distinguished R. marina from R. diptycha, identifying acoustic differences primarily in dominant frequency, maximum frequency, number of notes per call, and maximum frequency. The calls of R. marina comprise 135–272 notes, with maximum frequencies of 689–775 Hz and durations of 6.8–20 s. The calls of R. diptycha contained 17–93 notes, with maximum frequencies of 844–1119 Hz and duration of 0.5–7.2 s. Our findings align with previous studies on R. diptycha and R. marina, except for a population identified as R. diptycha from Natal, Brazil, which likely corresponds to R. marina from Brazil. Given the extensive distribution of the R. marina group species across South America, particularly in Brazil, we recommend reevaluating the calls of R. icterica, R. arenarum, R. rubescens, and R. cerradensis. Finally, we emphasize the need for comprehensive descriptions of the calls of R. achavali and R. veredas.